HPLC METHOD OPTIMISATION AND APPLICATION FOR THE ANALYSIS OF L(+) AND D(-) LACTIC ACID IN WINE - A WAY FOR ASSESSING WINE QUALITTY - Delia GLIGOR; Carmen ROBA; Gabriel KATONA; Csaba PAIZS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Because of their antioxidant, antimicrobial and anti-inflammatory properties, there is an increasing interest in investigating the presence of organic acids in food. The analysis of organic acids in wine is of great importance, considering their role in organoleptic and aesthetic character. In the present study, a high-performance liquid chromatographic (HPLC) method was optimised and applied for rapid analysis of L-lactic acid and D-lactic acid in wine samples. The enantiomer separation was performed on a chiral column, using an aqueous solution of CuSO2=4 as the mobile phase. After the optimisation, the method was applied for the quantification of lactic acid enantiomers in several red and white wine samples, collected from two private wineries from Romania. The concentration of L-lactic acid ranged between 0.79 and 1.24 g/l, while D-lactic acid was between 0.17 and 0.29 g/l.